2008
DOI: 10.1136/gut.2007.141481
|View full text |Cite
|
Sign up to set email alerts
|

Secreted enteric antimicrobial activity localises to the mucus surface layer

Abstract: These findings show that secreted antimicrobial peptides are retained by the surface-overlaying mucus and thereby provide a combined physical and antibacterial barrier to prevent bacterial attachment and invasion. This distribution facilitates high local peptide concentration on vulnerable mucosal surfaces, while still allowing the presence of an enteric microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
190
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(193 citation statements)
references
References 50 publications
3
190
0
Order By: Relevance
“…As bacteria must become mucosa associated before uptake by DCs for translocation to MLN or before invasion into the lamina propria, Paneth cells could limit bacterial penetration of host tissues by controlling the numbers of mucosa-associated bacteria. This idea is consistent with the fact that secreted Paneth cell antibacterial factors are retained by the mucus layer that overlies the intestinal epithelium, but are virtually absent from luminal content (29). This relatively impermeable mucus barrier may thus define a confined space that allows the host to specifically monitor and regulate bacteria that are in close contact with the intestinal surface.…”
Section: Discussionsupporting
confidence: 62%
“…As bacteria must become mucosa associated before uptake by DCs for translocation to MLN or before invasion into the lamina propria, Paneth cells could limit bacterial penetration of host tissues by controlling the numbers of mucosa-associated bacteria. This idea is consistent with the fact that secreted Paneth cell antibacterial factors are retained by the mucus layer that overlies the intestinal epithelium, but are virtually absent from luminal content (29). This relatively impermeable mucus barrier may thus define a confined space that allows the host to specifically monitor and regulate bacteria that are in close contact with the intestinal surface.…”
Section: Discussionsupporting
confidence: 62%
“…Then the surviving bacilli travel to the colon carried by the mucous flow, rich with HD5 and other AMPs (62), which constrains their replicative capacity and protects the host from C. difficile colonization. This hypothesis is supported by experiments showing that HD5 persists in an intact and functional form throughout the all intestinal tract, including the colon (52), and is active throughout a broad pH range (pH 5.5 to 8.0) (36).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these technical obstacles, a number of studies during the past decade have revealed the synthesis and structural organization of the mucus matrix and its critical role during homeostasis and antimicrobial host defense. [1][2][3] Using the mucus preserving Carnoy fixative, Matsuo et al and Swidsinski et al demonstrated the existence of a bacteria-free zone separating the enteric epithelium from the microbiota. [4][5] Later, Johansson et al showed the presence of bacteria within the outer, but not the inner, colonic mucus layer consistent with the finding that mucus represents an important nutrient source of enteric commensals.…”
mentioning
confidence: 99%
“…1,13 Immunostaining and proteomic analysis of the intestinal mucus identified lysozyme as well as a number of antimicrobial peptides with well-known antibacterial function in the mucus layer (see Table 1). …”
mentioning
confidence: 99%
See 1 more Smart Citation